Contestation in Prism
X, 199 p. 2 illus., 1 illus. in color.
Keywords: This book analyses the complex dynamics of international norm contestation and explores how norms adapt and withstand challenges in different settings. Examining the interplay between various types of contestation, norm robustness, and the resilience of norm clusters, it sheds light on what the authors define as ‘contestation in prism’. The book thus presents norm contestation as a multifaceted process with far-reaching implications. In this context, it further discusses different conceptions of contestation, ranging from reactive vs. proactive contestation and applicatory vs. validity contestation, to inadvertent, i.e. interpretive vs. deliberate contestation. It then develops a theoretical model that links contestation ‘in prism’ with studies of norm clusters, or norms that are embedded in broader normative structures and interwoven with other normative meanings. Based on a strong theoretical framing, the book presents in-depth analyses of norm contestation in areas such as regional organizations, nuclear non-proliferation, norms relating to atrocities, and international criminal law. Offering multifaceted perspectives on norm evolutions and their implications, this contribution will appeal to students, scholars, and researchers of international relations and related disciplines, as well as policy-makers interested in a better understanding of contestation and norm cluster resiliency.